Meningkatkan Aktivitas Belajar Dan Keterampilan Berpikir Kritis Menggunakan Kombinasi Model Problem Based Learning Dan Pendekatan Tpack Pada Muatan IPA Siswa Sekolah Dasar - Dewi Normaya; Maimunah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this research is the lack of science process skills, students do not work together, students' critical thinking skills are less developed, students do not understand the material, and learning has not integrated technology. The purpose of this study was to determine teacher activity, student activity, critical thinking skills and learning outcomes of fifth grade students at Kelayan Timur 8 Elementary School by applying the "Problem Based Learning and TPACK Approach" learning model. Classroom Action Research conducted during these 4 meetings is based on four stages, namely: (1) Planning (2) Action (3) Observing (4) Reflecting. The data in this study are the results of observations and written test results. The results of the study showed that the teacher's activities in 4 meetings were carried out very well. Student activity increases at each meeting, so that 100% of students are classically successful with active purification. Students' critical thinking skills improve at each meeting, so that 100% of students classically succeed in completing everything critically. Student learning outcomes increase at each meeting and 96% of students classically succeed in achieving the KKM.